Prototype Sistem Kontrol dan Monitoring Apron Flood Light Berbasis Website dengan Power Line Carrier Communication (PLCC) KQ 330 Sebagai Media Pembelajaran di Politeknik Penerbangan Jayapura - Musri Kona; Rifqi Raza Bunahri; Kevin Sari Megansa; Tiara Nugrahayani (Politeknik Penerbangan Jayapura, 2024)
In the aviation industry, effective control and monitoring of apron lights are crucial for flight operations. This project focuses on designing and implementing a website-based control and monitoring system for apron flood lights using Power Line Carrier Communication (PLCC) KQ 330, intended as a learning tool at Jayapura Aviation Polytechnic. The research method involves designing a system with components such as NodeMCU ESP8266, PLCC KQ 330 module, Arduino Uno, and other supporting elements, followed by functional and integration testing to ensure proper operation. Results demonstrate that the system can efficiently control and monitor apron flood lights via the website, offering convenience for electricians and Apron Movement Control (AMC) officers. The study concludes that the website-based system with PLCC KQ 330 enhances field efficiency and quality, while also serving as a valuable educational resource for students. Future research should focus on scaling up the system and integrating it with more complex airport infrastructures.